2021
DOI: 10.3390/ijms22179289
|View full text |Cite
|
Sign up to set email alerts
|

(20S) Ginsenoside Rh2 Inhibits STAT3/VEGF Signaling by Targeting Annexin A2

Abstract: Signal transducers and activators of transcription 3 (STAT3) acts as a transcriptional signal transducer, converting cytokine stimulation into specific gene expression. In tumor cells, aberrant activation of the tyrosine kinase pathway leads to excessive and continuous activation of STAT3, which provides further signals for tumor cell growth and surrounding angiogenesis. In this process, the tumor-associated protein Annexin A2 interacts with STAT3 and promotes Tyr705 phosphorylation and STAT3 transcriptional a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…55,56 A study in 2021 showed that using (20S) ginsenoside Rh2, a natural ginseng extract with anticancer activity, interfered with the interaction of ANXA2 and STAT3, and inhibited STAT3 phosphorylation, thereby inhibiting tumor development-related processes. 57 Furthermore, the phosphorylation of ANXA2 at Tyr-23 was confirmed to be necessary for ANXA2 monomer located on the cell membrane by using ANXA2 Tyr-23 mutant approach. 20 Tyrosine phosphorylation of ANXA2 is an important process in triggering Rho/Rho-associated coiled-coil-containing protein kinase(ROCK) pathway related to cell adhesion control.…”
Section: Anxa2 In Transforming Growth Factor (Tgf)-β Induced Emtmentioning
confidence: 91%
See 1 more Smart Citation
“…55,56 A study in 2021 showed that using (20S) ginsenoside Rh2, a natural ginseng extract with anticancer activity, interfered with the interaction of ANXA2 and STAT3, and inhibited STAT3 phosphorylation, thereby inhibiting tumor development-related processes. 57 Furthermore, the phosphorylation of ANXA2 at Tyr-23 was confirmed to be necessary for ANXA2 monomer located on the cell membrane by using ANXA2 Tyr-23 mutant approach. 20 Tyrosine phosphorylation of ANXA2 is an important process in triggering Rho/Rho-associated coiled-coil-containing protein kinase(ROCK) pathway related to cell adhesion control.…”
Section: Anxa2 In Transforming Growth Factor (Tgf)-β Induced Emtmentioning
confidence: 91%
“…As a result, E‐cadherin gene (CDH1) transcription was inhibited, and vimentin and MMP2/9 expression were upregulated, thereby promoting the pathological process of EMT 55,56 . A study in 2021 showed that using (20S) ginsenoside Rh2, a natural ginseng extract with anticancer activity, interfered with the interaction of ANXA2 and STAT3, and inhibited STAT3 phosphorylation, thereby inhibiting tumor development‐related processes 57 . Furthermore, the phosphorylation of ANXA2 at Tyr‐23 was confirmed to be necessary for ANXA2 monomer located on the cell membrane by using ANXA2 Tyr‐23 mutant approach 20 .…”
Section: How Does Anxa2 Participate In Epithelial‐mesenchymal Transit...mentioning
confidence: 99%
“…Overactivation of STAT3 can promote tumor growth either directly through tumor autonomic mechanisms or indirectly by modulating antitumor responses of tumor-associated stroma and immune system. Constitutively activated STAT3 in tumor cells not only eliminates anti-tumor immune response by continuously promoting IL-6 (91), IL-10 (91) or vascular endothelial growth factor (VEGF) (92) in the TME, but also transcribes and activates key oncogenes involved in immunosuppression such as programmed cell death-ligand 1 (PD-L1) (93), indoleamine 2, 3-dioxygenase 1 (IDO1) (94). The high expression of STAT3 thus enhances immune escape ability or establishes immune tolerance through a variety of mechanisms, and the inflammatory microenvironment further promotes tumor angiogenesis and the growth, invasion and metastasis of tumor cells (95).…”
Section: Stat3mentioning
confidence: 99%
“…Common clinical precancerous lesions of the GI tract include: chronic atrophic gastritis and gastric ulcer (GU), chronic hepatitis and cirrhosis, colon and rectal polyps, and epithelial hyperplasia. ( Wang Y et al, 2021 ).…”
Section: Prevention Of Precancerous Lesions By the Active Ingredients...mentioning
confidence: 99%